Simvastatin-Induced Acute Pancreatitis: A rare side effect of a statin - Suwansiripat, Somjate; Saengpattrachai, Montri; Shivawongsri, Sirijakorn; Choomduang, Piyarat; Kukreja, Rapin (The Bangkok Medical Journal, 2013)
Acute Pancreatitis is dened as the abrupt nonbacterial inammation of the pancreas. Typical symptoms comprise of abdominal pain located in the epigastrium and radiating to the back. In the majority of cases, the progression of acute pancreatitis is mild and self-limited. Albeit, one fth of patients may deteriorate and develop multiple organ dysfunction syndrome (MODS) which eventually enhance smortality rate.1,2 The rst and second most common etiologies, accounting for approximately 75% of cases in most developed countries, are gallstones and alcohol respectively.3 Less common causes include pancreatitis occurring after endoscopic retrograde cholangiopancreatography (ERCP), abdominal trauma, familial hypertriglyceridemia, hypercalcemia, autoimmune disease, toxins, etc.4,5 Drug-induced pancreatitis is a relatively rare occurrence, accounting for approximately 1.2-2% of cases.6-8 Of those, acute pancreatitis caused by the 3-hydroxy-3- methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors, often referred to as statins, has been reported rarely.9 We reported a case experiencing the very rare side effect of simvastatin-associated acute pancreatitis. This information should increase awareness of physicians and pharmacists not to overlook the etiology particularly in any patients diagnosed with idiopathic pancreatitis.